Comparing non-ischaemic heart preservation (NIHP) with ischaemic static cold storage of donor hearts in adult cardiac transplantation: study protocol for a randomised controlled trial - Johan Nilsson; Henry Pigot; Stig Steen (BMJ Open, 2025)
Introduction Ischaemia–reperfusion (I/R) injury remains a major challenge in heart transplantation, with mortality risk increasing significantly when allograft ischaemic time exceeds 4 hours. Non-ischaemic heart preservation (NIHP), using continuous hypothermic perfusion, has shown promise in preliminary studies for reducing I/R injury and improving outcomes. This randomised controlled trial aims to compare NIHP with standard static cold storage (SCS) in adult heart transplantation.Methods and analysis The trial is a prospective, open-label, multicentre, single-blinded, randomised controlled trial including 66 adult heart transplant recipients across four Swedish hospitals. Participants will be randomised into 1:1 ratio to NIHP or SCS preservation groups and undergo a 12-month follow-up period. The primary outcome is 1-year survival free from acute cellular rejection or retransplantation. Secondary outcomes include quality of life, I/R injury markers, graft function and adverse events. Substudies will evaluate renal function using MRI and continuously monitor physical activity and heart rhythm via wearable devices. Analysis will follow intention-to-treat principles, with time-to-event analysis using Cox proportional hazard models and Kaplan-Meier estimates.Ethics and dissemination The study has been approved by the Swedish Ethical Review Authority. It will be conducted according to the Declaration of Helsinki and relevant local and international regulations. Results will be published in peer-reviewed journals following Consolidated Standards of Reporting Trials guidelines.Trial registration number NCT04066127.